Estimation of evapotranspiration from UAV high-resolution images for irrigation systems in rice fields on the northern coast of Peru - Ramos-Fernandez, Lia (2024)
In view of the growing scarcity of water for agriculture, the increase in food demand and future drought scenarios posed by climate change, it is essential to design new technologies that contribute to lower water consumption. In this research, high-resolution images have been used to estimate evapotranspiration in rice fields by applying the METRICTM (Mapping Evapotranspiration at High Resolution using Internalized Calibration) energy balance model. For this purpose, 5900 m2 of crop were monitored under continuous flood irrigation (CF) and 2600 m2 under alternate wetting and drying irrigation (AWD), in addition to some plots with lateral filtration. Ten flights were conducted between tillering and flowering phases, five flights with a Matrice 210 UAV equipped with a Parrot Sequoia multispectral camera, and five flights with a Matrice 300 RTK equipped with a H20T thermal camera. Field data were collected from vegetation indices (NDVI and LAI), and readings from a radiometer, to adjust information from multispectral and thermal images, respectively, and to obtain the components of the surface energy balance. Mean values for crop evapotranspiration (ETc) of 6.34 ± 1.49 and 5.84 ± 0.41 mm d-1 were obtained for IC irrigation and AWD irrigation, respectively, obtaining a water saving of 42% with a yield reduction of 14%, providing a guide for proper irrigation management, however, it is suggested to use the model to optimize yield by obtaining critical thresholds for optimal application of AWD in the face of water resource scarcity. Keywords: Rice fields, AWD; Evapotranspiration; METRIC; UAV.